catena-Poly[[aquadipyridinecopper(II)]-μ-fumarato] - Xie, Dong (International Union of Crystallography, 2007)
The title compound, [Cu(C(4)H(2)O(4))(C(5)H(5)N)(2)(H(2)O)](n), is a one-dimensional coordination polymer based on pyridine and fumarate ligands. Each Cu(II) cation is coordinated by two carboxylate O atoms belonging to two fumarate anions, two N atoms from two pyridine molecules and one water molecule, in a square-based pyramidal geometry. Each fumarate anion bridges two Cu(II) cations through the two carboxylate groups in a bis-monodentate fashion to form a one-dimensional polymeric chain along the c axis. Neighbouring chains are linked together to form a two-dimensional network parallel to the ac plane via hydrogen bonding interactions between uncoordinated carboxylate O atoms and coordinated water molecules of adjecent chains.